A Critical Review on the Book Transformation of the Foundations of the Legitimacy of the Monarchy: From the Mongol Invasion to the Rise of the Safavids - Abdollah Sajedi; Hooshang Khosrobigi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The issue of legitimacy in the history of Iran is one of the issues that has attracted the attention of historians in recent decades. One of the most recent of these works is The evolution of the foundations of the legitimacy of the monarchy from the Mongol invasion to the rise of the Safavids. This work examines the evolution of the foundations of the legitimacy of this period in the context of a pervasive crisis of legitimacy in the form of multiple models, emphasizing that with the fall of the caliphate and the arrival of the Mongol element, the complexity of the foundations of legitimacy doubled and new inspiring foundations. It was raised for legitimacy. In addition, after the fall of the Ilkhanate, almost all special orders and organizations were damaged. Governments, with numerous features and characteristics, used various legitimizing models to justify their sovereignty. Thus, governments faced a crisis of legitimacy on the issue of the foundations of legitimacy. This article aims to critically review the above work. This study shows that the crisis of legitimacy was a major issue in the period under review, but the patterns of legitimacy were by no means based on a single pattern, but on a multifaceted, composite, and simultaneous pattern, but important indicators such as the Iranian idea of monarchy; Farah Izadi and Farah Kiani were ignored. The work is weak in terms of methodological foundations and definition of concepts and has not been able to conceptually design a comprehensive multidimensional model for the period.